EFEKTIVITAS PERAN BAPPEDA DALAM PEMBANGUNAN KOTA MEDAN - Oktalia Azmi Fadila; Mahrizal Mahrizal; Siti Khalijah (Universitas Teuku Umar, 2021)
AbstractBappeda is an important regional institution that has a function in the development of an area, where the successful assessment of the development of an area is assessed from Bappeda that performs its functions and duties well. During the Covid-19, Bappeda's role is very important in the development of Medan city, where Bappeda must carry out development in line with the Covid-19 protesters that hit the world. The presence of Covid-19 in Indonesia is very affecting in terms of economy and development, because of the rapid development of the virus that many people are exposed to. This caused many investors to change their investment plans in Indonesia and then impact the slump in the Indonesian economy. The impact of Indonesia's economic downturn is the delay in development that has been planned by Bappeda. In addition, Bappeda must also allocate funds while the pandemic is still running. All aspects of the point of view must be considered in the regional development plan that will be contained in the RPJMD and will be implemented by opd as soon as the opd performance will be evaluated by Bappeda then Bappeda will be accountable to the Mayor of Medan. In the implementation of development planning and in the implementation of it of course there are some obstacles that hinder regional development, therefore Bappeda must have prepared a solution of the planning. Keywords: Bappeda, Development Planning, Effectiveness.